2012
DOI: 10.5194/tc-6-51-2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MODIS-derived land surface temperatures with ground surface and air temperature measurements in continuous permafrost terrain

Abstract: Abstract. Obtaining high resolution records of surface temperature from satellite sensors is important in the Arctic because meteorological stations are scarce and widely scattered in those vast and remote regions. Surface temperature is the primary climatic factor that governs the existence, spatial distribution and thermal regime of permafrost which is a major component of the terrestrial cryosphere. Land Surface (skin) Temperatures (LST) derived from the Moderate Resolution Imaging Spectroradiometer (MODIS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 43 publications
5
97
0
1
Order By: Relevance
“…Hall et al 2012), to monitor melt events on the ice sheet (Hall et al, 2013), and as input for surface mass balance or snowpack modeling (Fréville et al, 2014;Shamir and Georgakakos, 2014;Navari et al, 2016). A number of validation studies present results acquired over various time scales and in different locations to 130 determine the accuracy of the MODIS surface temperature products in the cryosphere (Hall et al, 2004(Hall et al, , 2008Koenig and Hall, 2010;Westermann et al, 2012;Hachem et al, 2012;Shuman et al, 2014;Østby et al, 2014;Shamir and Georgakakos, 2014;Hall et al, 2015;Williamson et al, 2017). validation studies and is discussed in further detail in the discussion section.…”
Section: Remote Sensing Of Surface Temperaturementioning
confidence: 99%
“…Hall et al 2012), to monitor melt events on the ice sheet (Hall et al, 2013), and as input for surface mass balance or snowpack modeling (Fréville et al, 2014;Shamir and Georgakakos, 2014;Navari et al, 2016). A number of validation studies present results acquired over various time scales and in different locations to 130 determine the accuracy of the MODIS surface temperature products in the cryosphere (Hall et al, 2004(Hall et al, , 2008Koenig and Hall, 2010;Westermann et al, 2012;Hachem et al, 2012;Shuman et al, 2014;Østby et al, 2014;Shamir and Georgakakos, 2014;Hall et al, 2015;Williamson et al, 2017). validation studies and is discussed in further detail in the discussion section.…”
Section: Remote Sensing Of Surface Temperaturementioning
confidence: 99%
“…Such requirements are, however, extremely difficult to fulfill at Arctic sites, where logistical constraints limit the number of field stations. Hachem et al (2012) compared MODIS LST to ground and air temperatures over herbaceous and shrub tundra sites across North America. MODIS LST errors found by Hachem et al (2012) are in the range of errors found in this study.…”
Section: Uncertainties and Errors Of Modis Lst Evaluationmentioning
confidence: 99%
“…Hachem et al (2012) compared MODIS LST to ground and air temperatures over herbaceous and shrub tundra sites across North America. MODIS LST errors found by Hachem et al (2012) are in the range of errors found in this study. Alternatively to radiometer measurements, measurements of near-surface ground and air temperature might therefore serve as validation data for MODIS LST.…”
Section: Uncertainties and Errors Of Modis Lst Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomlinson et al [12] compared the nighttime LST from MODIS with ground-measured air temperature across a conurbation and found that the measured air temperature was always greater than the MODIS-derived LST. Hachem et al [26] found that the mean daily LST was more strongly correlated with near-surface air temperature in an area with continuous permafrost when the TERRA/AQUA MODIS data were combined than when these values were considered separately (TERRA or AQUA, daytime or nighttime). Zhu et al [13] showed that daily maximum and minimum air temperatures could be retrieved effectively from MODIS LST products by using temperature-vegetation index method in the Xiangride River basin of the northern Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%